SUBVERSIÓN Y ESPECTÁCULO: LA ANTIPOESÍA DE NICANOR PARRA. - Morales Toro, Leonidas (Revista Chilena de Literatura, 2015)
This article proposes to consider Nicanor Parra's poetic work produced after Sermones y prédicas del Cristo de Elqui, that is from the 1980s onwards, as postmodern. Following this consideration, this postmodern work can be intellectively apprehended from Jameson's concept of "pastiche" as imitation of itself. The development of the critical argumentation takes into account diverse aspects of Parra's work, such as signs, discursive structures, and visual images.